Introduction to networks. (Cisco Press, 2013)
The official supplemental textbook for the Introduction to Networks course in the Cisco® Networking Academy® CCNA® Routing and Switching curriculum. The course introduces the architecture, structure, functions, components, and models of the Internet and computer networks. The principles of IP addressing and fundamentals of Ethernet concepts, media, and operations are introduced to provide a foundation for the curriculum. By the end of the course, you will be able to build simple LANs, perform basic configurations for routers and switches, and implement IP addressing schemes. The Companion Guide is designed as a portable desk reference to use anytime, anywhere to reinforce the material from the course and organize your time. The book's features help you focus on important concepts to succeed in this course: Chapter Objectives -Review core concepts by answering the focus questions listed at the beginning of each chapter. Key Terms -Refer to the lists of networking vocabulary introduced and highlighted in context in each chapter. Glossary -Consult the comprehensive Glossary with more than 195 terms. Summary of Activities and Labs -Maximize your study time with this complete list of all associated practice exercises at the end of each chapter. Check Your Understanding -Evaluate your readiness with the end-of-chapter questions that match the style of questions you see in the online course quizzes. The answer key explains each answer. Related Title: Introduction to Networks Lab Manual ISBN-10: 1-58713-312-1 ISBN-13: 978-1-58713-312-1 How To -Look for this icon to study the steps you need to learn to perform certain tasks. Interactive Activities -Reinforce your understanding of topics with more than 50 different exercises from the online course identified throughout the book with this icon. Packet Tracer Activities -Explore and visualize networking concepts using Packet Tracer exercises interspersed throughout the chapters. Hands-on Labs -Work through all 66 course labs and Class Activities that are included in the course and published in the separate Lab Manual. This book is part of the Cisco Networking Academy Series from Cisco Press®. Books in this series support and complement the Cisco Networking Academy curriculum.